Crossing university boundaries: Students' experience of PBL as a new epistemic game - Kirsten Jæger (Globe, 2020)
Today, educational trajectories take university students through a range of different institutional and organizational contexts. Many students choose to earn their master’s degree at a university different from their bachelor university. This increased mobility causes many students to cross university borders, both nationally and internationally. While the principles of collaborative learning, student-centered pedagogic approaches, and engagement with real-life problems are now widely applied principles at most universities, and are also promoted through large-scale transnational policy processes such as the Bologna Process, a few universities have demonstrated their strong commitment to such principles by dedicating themselves to the pedagogic approach of problem-based learning (PBL). This commitment may further internal cohesion and the development of a distinct and recognizable identity. In other words, a university’s commitment to the teaching and learning philosophy of PBL creates identity boundaries (Santos & Eisenhardt 2005). This study explores the experience of students who cross these boundaries and make an effort to learn PBL, in other words, to study in a PBL context. Theoretically, PBL is understood as an overarching epistemic game (Perkins 1997; Markauskaite & Goodyear 2017a) that students seek to master. The empirical investigation was carried out at a PBL university that strongly encourages group work. Three focus group interviews were conducted at two different points in the project-writing period: once mid-term, when the project work was ongoing, and at a later point right after the (collective) oral defense of the project work. The findings suggest that while students seek to identify clear and manifest rules of the epistemic game of PBL, supervisors and censors expect students to be able to “learn through design of inquiry” (Markauskaite and Goodyear 2017b), in other words, to make their own choices regarding the epistemic framework.